The Gastrointestinal Bacteria of Mink (Mustela vison L): Influence of Age and Diet - Williams, C. (Acta Vet Scand, 1998)
Total numbers of aerotolerant and anaerobic bacteria, and densities of Enterobacteriaceae, lactobacilli, staphylococci, salmonella and shigella, and campylobacteria were enumerated in the contents of the stomach, small intestine (and the associated mucosa), and colon of mink beginning at 2 weeks of age to adulthood, and in adults that were fed diets with different levels and types of fiber or food deprived. Highest densities of all bacterial groups were found in the colon at all ages (up to 10(8) cfu per g for total anaerobes), but were 2–4 orders of magnitude lower than those of other mammals. When all regions were pooled, significant age-related increases (p<0.05) were detected for anaerobes, aerobes, and staphylococci, and these coincided with the dietary shift at weaning. Enterobacteriaceae did not vary with age. Lactobacilli were never common isolates, but were detected more often after weaning, particularly in adults fed diets containing the 2 sources of fiber. Campylobacteria were detected only at 2 weeks of age, and salmonella and shigella were not isolated from any of the experimental mink. Total bacterial densities, the relative proportions of the bacterial groups, and age- and diet-related effects differ from those known for other mammals, which may be related to the carnivorous diet and rapid movement of digesta through the GIT.